Numerical and Experimental Vibration Analysis of a Steam Turbine Rotor Blade - Katinić, Marko; Ljubičić, Marko (2021)
Damage to the rotor blade of a steam turbine is a relatively common problem and is one of the leading causes of sudden and unplanned shutdowns of a steam turbine. Therefore, the high reliability of the rotor blades is very important for the safe and economical operation of the steam turbine. To ensure high reliability, it is necessary to perform a vibration analysis of the rotor blades experimentally and in a computer environment. In this paper, a modal analysis was performed on the twisted blade of the last stage of the turbine in the Ansys software. The results of the modal analysis of the stationary rotor blade were compared with the results obtained by the bump test, which confirmed the numerical model of the blade. A modal analysis of a rotating rotor blade was performed on the same numerical model, and Campbell diagrams were plotted to determine the critical speed
Bibliografija
Summary.